Carceral racialization, prison segregation, and the Integrated Housing Program in Arizona - Bloch, Stefano (Theoretical criminology, 2024)
Prisoners in the Arizona Department of Corrections, Rehabilitation, and Reentry (ADCRR) coordinate to circumvent full racial housing integration, revealing how “race” and adherence to the “racial code” is used as an organizing concept in carceral settings that is distinct from conceptualizations of race and politics of identity within free society. In addition to providing a review of the literature on the complexity of prison racialization, we base our discussion of racialization and adherence to the racial code on our combined experience as formerly racialized and gang-affiliated inmates, as well as on insights from informal and semi-structured interviews with prisoners who have navigated attempts at racial integration as part of the ADCRR's recently adopted Integrated Housing Program.